Investigating quality service and student satisfaction: evidence from College of Business & Economics, University of Gondar, Ethiopia - Getahun Demis Alamirew (Journal of Innovation and Entrepreneurship)
Abstract Providing quality service is the major concern of many public organizations. However, the way to provide immediate service (responsiveness), the capacity to deliver on promises of accurate and consistent service (reliability), the degree of trust and confidence of students in the service provided by the college (assurance), the physical appearances of the service that the college offers (tangibility) and understanding the needs of students in the college are not as such potential. Thus, the study aims to investigate the effect of a quality service system on student satisfaction in Business and Economics College, University of Gondar. An explanatory research design with a quantitative research approach was employed to address the specified objectives. The population of the study was 6323 and out of these, 376 samples were drawn through stratified random sampling technique. Of 376 self-administer questionnaires, 263 were valuable for this analysis. One of the objectives of the study was to understand the dominant service quality dimension. The finding of the mean score of SERVQUAL dimensions portrays that students are less satisfied with dimension responsiveness (M = 2.31), which implies that the way students get an immediate response for their need showed very low followed by dimension empathy (M = 2.63) i.e., the willingness of staff to support or help students, spontaneous care and concern of staff to student’s needs, is lower, whereas with tangibles, assurance, and reliability are better. The PLS-SEM analysis result confirmed that tangibility and assurance has a significant effect but other service quality dimensions are not.